Therapeutic Communities, drugs, and the Public Fund dispute - Passos, Rachel Gouveia; Gomes, Thatiana Meyre da Silva; Araujo, Giulia de Castro Lopes de; Moreira, Ana Luiza Almeida (Argumentum, 2023)
This article analyses the distinctiveness of Rio de Janeiro in the dispute for public funds for Therapeutic Communities (TCs), as they are advancing different portfolios and occupying important positions. This qualitative analysis is based on a study of legislation, bibliographies, news items, and minutes of events on the subject, aiming to question the management of the public budget in the municipality of Rio de Janeiro between the years 2019 and 2022, where the TCs managed to transition between secretariats and capture public resources to finance vacancies via public notices. This article is divided into three topics: the first is a brief conceptual review of the public fund and its capture by capital; the second presents the history of, and characterises, Brazilian TCs; and finally, the third analyses the dynamics of the process of securing public funds by these institutions in the city of Rio de Janeiro.